The Quality of Public Finance in the Countries of South-East Europe - Ivana Vukčević; Radislav Jovović (Journal of Central Banking Theory and Practice, 2020)
The subject of this research is to analyze a number of factors that impact the quality of public finances in the selected post-socialist South East countries (SEE). In the theoretical part of the paper we have selected and analyzed the factors (variables). The following key factors of influence (as independent variables) were included: socialist heritage, politicization as an abuse of macroeconomic policies, instability of institutional environment, human capital deficits in the area of public finances, and financial accountability deficits. In the quantitative part, the level of selected factors was assessed on the quality level of public finances in the observed countries. The hypothesis was that the factors selected had a very significant impact on the quality of public finances. Mathematical model based on multiple linear regression analysis was created in order to explain the functional relationship between the dependent variable: the quality level of public finances and the selected independent variables. The goal is to estimate the expected mean of the dependent variable (Y) based on individual estimates of the respondents. Regarding the respondent's perception, the Likert scale (1.0, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5,0) was used, where 1.0 indicates the lowest impact and 5.0 indicates the highest impact. Based on their best knowledge, experience, and (or) intuition, the respondents were asked to assess the dependent variable in the model and independent variables. The empirical data obtained, qualitative and quantitative, have confirmed the hypothesis.
Keywords: E40; E50; 330; public finances; institutional environment; SEE countries; financial responsibility.